PENGUKURAN KOMPONEN-KOMPONEN MESIN BUBUT DENGAN MENGGUNAKAN METODE SCHLESINGER - Slamet Riyadi; Rochim Suratman; Muki Satya Permana (PROCEEDING STIMA)
This Study aims to determine the operational feasibility of a machine tool through testing components based method lathe with Schlesinger, by taking objects on a lathe Tonk-Il is in a private company in the city of Bandung. The test includes measurement of the flatness of the bed, moved the motion alignment measurement head relative to the motion moved off the sledge, the measurement accuracy of the main spindle, the axis alignment measurement launchers outside the head off the sledge motion, precision spindle bearing carrier for Keming the press. Measurement of components lathe testing that can be done due to lack of measurement tools that can support the implementation of other measures. To memngetahui how irregularities after testing the characteristics on a lathe by using the method of Schlesinger. From the measurement results of the five types of testing that has been done shows that the lathe types of Tong-Il is in a private company in the city fit for use in accordance with the method of Schlesinger, in other words, has the capability and reliability to produce a product or workpiece with high accuracy.Keywords : Precision Machine Tool Geometry .